Predictive value of triglyceride glucose index in non-obese non-alcoholic fatty liver disease - He Liu; Fang Sun; Xiaopeng Zhu; Xia Gao; Juan Deng; ZhongYan Luo; Yijian Sun; Liqi Fan (BMJ Open)
Objectives A large number of patients with non-obese non-alcoholic fatty liver disease (NAFLD) in China remain undiagnosed and untreated due to insufficient awareness and ineffective pharmacotherapy. Therefore, a convenient, predictive marker and diagnostic tools are imperative. This study aimed to investigate the ability of the triglyceride glucose index (TyG) in predicting non-obese NAFLD.Design An observational cross-sectional study.Setting Department of Health Management, large urban academic medical centre and DRYAD database data.Participants This study included 456 patients with non-obese NAFLD and matched 456 non-fatty liver controls according to age, sex and body mass index (BMI).Primary and secondary outcome measures The receiver operating characteristic (ROC) curve was used to evaluate the predictive role of the TyG index in non-obese NAFLD. Based on the TyG index, a clinical prediction model for non-obese NAFLD was constructed, then the prediction model was verified by the DRYAD database (n=11 562).Results TyG in non-obese NAFLD was higher than that in controls (9.00 (8.66–9.40) vs 8.46 (8.10–8.83), p<0.001). Logistic regression analysis showed that TyG was an independent risk factor for non-obese NAFLD (OR=9.03, 95% CI: 5.46 to 14.94, p<0.001). ROC analysis showed that the area under the curve (AUC) was 0.78, the sensitivity was 82.5%, the specificity was 60.5%. Based on the TyG index, sex, age and BMI, the AUC of the predictive model for non-obese NAFLD was 0.78 (95% CI: 0.75 to 0.81, p<0.001). Using the DRYAD database to verify the prediction model, the AUC of the verification group was 0.85 (95% CI: 0.84 to 0.86, p<0.001).Conclusions The high level of the TyG may be an independent risk factor for non-obese NAFLD. The prediction model for non-obese NAFLD based on the TyG index has good clinical prediction value.